Role of Brassinosteroid on Qualitative Characteristics Improvement of Strawberry Fruit cv. Paros - soheila mohammadrezakhani; zahra pakkish; Somaye Rafeii (Majallah-i ̒Ulum-i Bāghbānī, 2017)
Introduction: Recently, strawberry growers have been mostly interested in growing cultivars for the fresh market because of its profitability, but on the other hand it requires more complicated technologies and well-educated workers. High quality of the fruit for the fresh market is an important factor attracts customers and determines their choice and prices. Fruit production cost for the fresh market needs to be calculated and efficient methods and technologies also should be taken into consideration. New environmentally friendly mineral-organic fertilizers can improve fruit quality and yield of dessert strawberry cultivars. The desired effects was obtained through the activity of fertilizer’s components, which very often belong to different groups of natural hormones, elicitors, vitamins, flavonoids, amino acids, etc. Numerous breeding programs have been aimed at improving strawberry taste and disease resistance. Three major components of fruit organoleptic quality are flavor, sweetness, and acidity. Several studies have been devoted to strawberry aroma. Fruit with intense flavor also have high titratable acidity and high soluble solids. Numerous studies have addressed strawberry sweetness and acidity. Fruit soluble solids, sugars, titratable acidity, and organic acids at maturity are quantitatively inherited. Moreover, there appears to be genetic variations for these fruit quality traits. Numerous biochemical changes are observed during strawberry development and especially during fruit ripening. The major soluble constituents of maturing and ripe strawberries are soluble sugars and organic acids. The major soluble sugars in strawberries are glucose, fructose, and sucrose. The major organic acid is citric acid. This acid contributes greatly to fruit titratable acidity, which declines gradually during fruit development. The sugar/ organic acid ratio is a major parameter of strawberry taste. Brassinosteroids (BRs) are a class of poly hydroxyl steroids, which have been recognized as a class of plant hormones. These were first explored when Mitchell et al. (1970) reported that cell division and elongation were promoted by the treatment of organic extracts of rape (Brassica napus L.) pollen. Brassinolide (BL) was the first isolated brassinosteroid when Michael et al. (1979) isolated the biologically active molecule. Researches showed that brassinosteroids are essential for many physiological functions in plants, however little is known concerning where and when they are synthesized. In young tomato seedlings BR synthesis activity was observed mainly in apical and root tissues undergoing expansion. In flowers, synthesis activity was observed in the pedicel joints and ovaries, whereas in the fruits it was strongest during early seed development and was associated with the locular jelly and seeds. Quantitative measurements of endogenous BR indicated intense biosynthesis in developing tomato fruits, which were also found to contain high amounts of brassinolide. Moreover, brassinosteroids stimulate cell elongation and cell division, and BR has a specific effect of differentiation. Underling physiological pathways include modification of cell wall properties, effects on carbohydrate assimilation, allocation, and control of aquaporin activities. Brassinosteroids apparently coordinates and integrates diverse processes required for growth, partly via interactions with phytohormones setting the frame for BR responses. The aim of present study was investigation of the role of brassinosteroid on qualitative characteristics improvement of strawberry fruit. Materials and Methods: In this research the effect of different concentrations (0, 0.25, 0.50, 0.75 and 1 mgl-1) of brassinosteroid sprayat different stages of strawberry growth (30 days after planting, first blooming, green fruit, and pink fruit) on some qualitative characteristics of the strawberry Paros cultivar was considered. This experiment was conducted asfactorial on a randomized complete block design with 4 replications in greenhouse conditions. Parameters such as total soluble solid, inducing sugar, titrable acidity, anthocyanin, phenol, fruit dry weight, fruit water and vitamin C were measured after…. Results and Discussion: Results showed treated plants by brassinosteroid, compared to control, improved fruit qualitative characteristics. So, brassinosteroid application increased total soluble solid, inducing sugar, titratable acidity, anthocyanin, phenol, dry weight, vitamin C.The best effective treatment and the best spraying time was brassinosteroid at 1 mgl-1 in pink fruit stage, respectively for qualitative characteristics improvement. Because, Brassinosteroid growth induced has been related to increase in RNA and DNA content, polymerase activity, protein synthesis carbohydrate fraction, reducing sugars, non-reducing sugars and starch. The yield increase in fruit trees may be related to improvement in the assimilation efficiency of photosynthetic carbon of the sprayed trees. The brassinosteroid application in wheat and mustard plants stimulated photosynthetic activity expressed by acceleration in CO2 fixing, increase protein biosynthesis and in mustard, increased photosynthetic rates that were directly related to growth and seed production. In accordance, researchers explained that BRs have been shown to enhance tracheary element differentiation, stimulate membrane hyperpolarization and ATPase activity, promote ethylene biothynsesis, control microtubule orientation and alter the mechanical properties of cell walls. In addition, brassinosteroid treatment greatly stimulated accumulation of photosynthates in the treated internode. This suggests a possible mobilization role for BR in the intact plant. As well as, in persimmon, grapevine and citrus, reported that BR compound showed, the practical effects for fruit setting. While, showed that brassinolide increased fruit weight and sugar content of oranges. In passion fruit orchards, brassinosteroid increased fruit number of plant and in turn yield per hectare and soluble solids content was 1° Brix greater than the control. Conclusions: From this study, it is evident that the application of plant biostimulants such as brassinosteroid significantly improved qualitative characteristics. So, brassinosteroid application increased total soluble solid, inducing sugar, titrable acidity, anthocyanin, phenol, dry weight, vitamin C and effective treatment and best spraying was brassinosteroid at 1 mgl-1 at pink fruit stage for qualitative characteristics improvement.